Exploring veterinary students’ awareness and perception of zoonoses risks, infection control practices, and biosecurity measures in Ethiopia - Nyokabi, Ndungu S.; Phelan, Lisette; Lindahl, Johanna F; Berg, Stefan; Muunda, Emmanuel; Mihret, Adane; Wood, James L. N.; Moore, Henrietta L. (Frontiers in Veterinary Science, 2024)
Universities and colleges are often regarded as playing a key role in educating veterinarians and animal health workers who advise farmers on herd health and animal husbandry. However, to date, studies examining veterinary students’ knowledge of zoonotic diseases of public health importance and the source of this knowledge, as well as their preparedness to respond to these diseases, have focused on the Global North rather than the Global South. This study takes Ethiopia as a case study in exploring veterinary medicine students’ knowledge of zoonosis risks, infection control practices and biosecurity measures, recognizing that it is imperative to reconcile national-level veterinary education curricula with emerging global trends, such as One Health-focused training. This training advocates for a collaborative, interdisciplinary response at local, national, and international levels to the adverse impact of zoonotic diseases on animal health and productivity, and human and environmental health. Data for this study were collected through a pre-tested online questionnaire administered to 154 veterinary students from several universities in Ethiopia. The findings of this study suggest veterinary students were aware of the public health risks posed by zoonoses and the important role that collaboration between the disciplines of human and animal health can play in addressing zoonoses and emerging health risks. However, students demonstrated poor knowledge of the need to adopt infection control measures (ICPs) and biosecurity measures to reduce occupational risks and prevent within and between herd transmission of infection. Moreover, students’ vaccination rates against zoonotic diseases associated with occupational risks, such as rabies, were low. The results of this study suggest that there are currently gaps in Ethiopia’s veterinary curriculum and that enhancing veterinary students’ access to information regarding infection control practices and biosecurity measures could contribute to reducing their future occupational exposure to zoonoses. This study highlights the policy implications of the current veterinary medicine curriculum in Ethiopia and the scope for aligning the curriculum with important global initiatives, such as One Health-focused training.